Ellen Battelle Dietrick: A Nineteenth Century Minimalist - Gruber, Mayer Irwin (Tyndale bulletin, 2003)
Revisionist historicism dates most Hebrew Scripture to the Hasmonean Era. Elizabeth Cady Stanton’s plea that heroines should be named suggests that credit for the revisionist thesis be given to Ellen Battelle Dietrick, who expounded it in 1895. Moreover, Dietrick’s exposition fully displays the eisegetical method by which the revisionist claim is read into 2 Maccabees.